Echinacea purpurea Ethanol Extract Improves Male Reproductive Dysfunction With Streptozotocin–Nicotinamide-Induced Diabetic Rats - Mao, Chien-Feng; Sudirman, Sabri; Lee, Chi-Chih; Tsou, David; Kong, Zwe-Ling (Frontiers in Veterinary Science, 2021)
As lifestyle changes, the prevalence of diabetes increases every year. Diabetes-induced male reproductive dysfunction is predominantly due to increased oxidative stress and then results in sperm damage and infertility. Echinacea purpurea is a traditional medicinal herb and is well-known for its immune-modulatory, antioxidative, anti-inflammatory, anticancer, and antiviral activities. The Toll-like receptor 4 (TLR4) plays a critical role in innate immune responses leading to nuclear factor (NF)-κB phosphorylation and release of proinflammatory cytokines including nitric oxide (NO), interleukin (IL)-1β, and tumor necrosis factor (TNF)-α. However, the relation between Echinacea purpurea extract and TLR4 remains unclear. This study aimed to investigate the protective effects on male reproduction of Echinacea purpurea ethanol extract (EPE) against diabetic rats and whether the anti-inflammatory effects were through the TLR4 pathway. Diabetic male Sprague–Dawley (SD) rats were induced by streptozotocin (65 mg/kg) and nicotinamide (230 mg/kg). EPE was tested in three doses (93, 279, and 465 mg/kg p.o. daily) for 4 weeks. Besides, metformin administration (100 mg/kg/day) was treated as a positive control. Results indicated that EPE administration for about 4 weeks improved hyperglycemia and insulin resistance. Additionally, EPE increased sperm motility, protected sperm morphology and mitochondrial membrane potential, as well as protein for testosterone synthesis enzyme. In sperm superoxide dismutase, catalase, and glutathione antioxidants were increased, whereas proinflammatory cytokines, such as NO, IL-1β, and TNF-α were decreased. The testis protein content of TLR4 and downstream phospho-NF-κB p65 also were reduced. The EPE might reduce the production of proinflammatory cytokines via TLR4 pathways and improve diabetes-induced male infertility.